ECtHR: Kulák v. Slovakia (Application no. 57748/21, 3 April 2025) - Igor Hron; Zuzana Mlkvá Illýová (Bratislava law review (Online), 2025)
The European Court of Human Rights (ECtHR) judgment in Kulák v. Slovakia addresses critical deficiencies in the Slovak criminal procedure, namely the protection of legal professional privilege during searches and seizures of electronic data. The case arose from a 2020 warrantless search of a lawyer’s office, where authorities seized the applicant’s entire work computer under an emergency provision. The ECtHR ruled that Slovakia’s reliance on prosecutorial oversight – rather than independent judicial review –failed to meet standards under Article 8 ECHR. This commentary begins by examining the factual background of the case and legal findings of the ECtHR. Subsequently, it evaluates the broader impact of the Kulák judgment and identifies remaining gaps and potential implications for other Council of Europe member states, advocating for independent oversight, and timely judicial remedies to uphold the rule of law.